1990
DOI: 10.1007/bf01959535
|View full text |Cite
|
Sign up to set email alerts
|

Parental smoking and asthma in childhood

Abstract: The effect of parental smoking on childhood asthma was investigated in which data from 302 asthmatic and 433 healthy children aged 1 to 12 years, were studied. All asthmatic patients received prick tests for common allergens. A significantly higher number of heavy parental smokers was found in asthmatic children under 6 years of age with negative prick tests (P = 0.02). A stepwise logistic regression was performed in order to verify interactions between parental smoking and other variables. It is concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…An American case-control study which measured urinary cotinine levels found a positive association with wheezing before the age of two years, but a non-significant inverse relationship thereafter 41. An Italian case-control study compared the effect of parental smoking before and after six years of age 22. The odds ratios for either parent smoking were 1.13 (95% CI 0.71 to 1.80) and 0.83 (95% CI 0.48 to 1.44), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An American case-control study which measured urinary cotinine levels found a positive association with wheezing before the age of two years, but a non-significant inverse relationship thereafter 41. An Italian case-control study compared the effect of parental smoking before and after six years of age 22. The odds ratios for either parent smoking were 1.13 (95% CI 0.71 to 1.80) and 0.83 (95% CI 0.48 to 1.44), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A number of risk factors for obstructive LRD besides heredity have been identified in children, such as viral infections [7][8][9], environmental tobacco smoke [10][11][12][13][14], damp and cramped housing [15][16][17] and socio-economic factors [18], whereas breast-feeding seems to be protective [19][20][21][22].…”
mentioning
confidence: 99%
“…Despite many reports over the years, the disaster continues [6,10,13,15]. Tobacco companies have undermined and discredited the scientific consensus that passive smoking causes diseases (a three-judge panel of the Washington, DC, US Court of Appeals unanimously upheld a lower court ruling on Pediatricians should not hesitate to label tobacco as the most frequent agent of child maltreatment despite the lack of intentionality of the child's carers.…”
mentioning
confidence: 99%
“…They have double the rate of respiratory disorders than children living in a smoke-free environment. Even if a child does not suffer from asthma but lives with parents who both smoke, he or she will show a 40% higher probability of having bronchitis, pneumonia, or bronchiolitis [10,14]. Learning and behavioral development may be impaired because of frequent absences from school.…”
mentioning
confidence: 99%